2005
DOI: 10.1111/j.1741-2358.2005.00059.x
|View full text |Cite
|
Sign up to set email alerts
|

Relationship of number of remaining teeth to health‐related quality of life in community‐dwelling elderly

Abstract: The findings of the present study indicated that 85-year-old participants with > or = 20 teeth had better subjective physical health than those with < or = 19 teeth.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
72
1
4

Year Published

2007
2007
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 83 publications
(86 citation statements)
references
References 35 publications
9
72
1
4
Order By: Relevance
“…Others describe QoL as representing physical function, health status, perceptions, behavior, lifestyle, and social functioning (Frytak 2000;Moons 2004;O'Boyle 1997). Evidence from the review showed that HRQoL and QoL were measured by many of the same broad domains and content areas (Akifusa et al 2005;Berkman 1999), a finding also supported by Brown et al (2004).…”
Section: Definitions Of Qolsupporting
confidence: 67%
See 2 more Smart Citations
“…Others describe QoL as representing physical function, health status, perceptions, behavior, lifestyle, and social functioning (Frytak 2000;Moons 2004;O'Boyle 1997). Evidence from the review showed that HRQoL and QoL were measured by many of the same broad domains and content areas (Akifusa et al 2005;Berkman 1999), a finding also supported by Brown et al (2004).…”
Section: Definitions Of Qolsupporting
confidence: 67%
“…Interpretability, as evidenced by normative comparisons, was reported for the SF-36, SF-12, LGC and the EuroQol (Akifusa et al 2005;Berkman 1999;Borglin et al 2005;Byles 1999;Byles et al 2004;Peek 2004;Stenzelius et al 2005;Tidermark et al 2004). 2,6,7,13,14,16,17,19,23,25,28,32,37,38,39,41 Study number as appears in Table 1 a Wilson and Cleary 1995 2,6,7,13,14,16,17,19,23,25,28,32,37,38,39,41,46 Special considerations for the assessment of QoL among older adults Special considerations given to domain coverage, agespecific areas, cognitive status, and administration method and instrument adaptation were reviewed.…”
Section: Psychometric Properties Reliability and Validitymentioning
confidence: 99%
See 1 more Smart Citation
“…Elderly patients with more than 20 remaining teeth experience a superior subjective physical health score to those with less than 20 teeth [2]. In highly developed mammals, teeth are a limiting life factor, as they are necessary for nutrition.…”
Section: Introductionmentioning
confidence: 99%
“…In other words, these observations suggested that there might be some relation between physical activity and HR-QOL. On the other hand, Akifusa et al ( 16 ) suggested that 85-y-old participants with 20 teeth or more have better subjective physical health than those with 19 or fewer teeth. In addition, Keller et al ( 17 ) suggested that weight reduction and malnutrition are associated with poor activity of daily living (ADL) measurements and life dissatisfaction in the elderly.…”
mentioning
confidence: 99%